Homosexuelle im Nationalsozialismus. Neue Forschungsperspektiven zu Lebenssituationen von lesbischen, schwulen, bi-, trans- und intersexuellen Menschen 1933 bis 1945 - Schwartz, Michael 1963- (Zeitgeschichte im Gespräch, 2014)
How did homosexual, bisexual, transsexual, and intersexual persons live during the Nazi era? What persecutory measures did they face? This compendium addresses these and other questions. A focus is placed on the police and justice system as well as political, administrative, and social repression